The origin of the flatbed scanner artifacts in radiochromic film dosimetry—key experiments and theoretical descriptions. (14th October 2016) - Schoenfeld, Andreas A; Wieker, Soeren; Harder, Dietrich; Poppe, Bjoern
Abstract: The optical origin of the lateral response and orientation artifacts, which occur when using EBT3 and EBT-XD radiochromic films together with flatbed scanners, has been reinvestigated by experimental and theoretical means. The common feature of these artifacts is the well-known parabolic increase in the optical density OD( x )  =  −log10 I ( x )/ I 0 ( x ) versus offset x from the scanner midline (Poppinga et al 025 Med. Phys .41 021707). This holds for landscape and portrait orientations as well as for the three color channels. Dose-independent optical subjects, such as neutral density filters, linear polarizers, the EBT polyester foil and diffusive glass, also present the parabolic lateral artifact when scanned with a flatbed scanner. The curvature parameter c of the parabola function OD( x )  =   c 0   +   cx 2 is found to be a linear function of the dose, the parameters of which are influenced by the film orientation and film type, EBT3 or EBT-XD. The ubiquitous parabolic shape of function OD( x ) is attributed (a) to the optical path-length effect (van Battum et al 033 Phys. Med. Biol .61 625–49), due to the increasing obliquity of the optical scanner light associated with increasing offset x from the scanner midline, and (b) and (c) to the partial polarization and scattering of the light leaving the film, which affect the ratio   I ( x ) / I 0 ( x ), thus making OD( x ) increase with x 2 . The orientation effect results from the changes of effects (b) and (c) associated with turning the film position, and thereby the orientation of the polymer structure of the sensitive film layer. In a comparison of experimental results obtained with selected optical subjects, the relative weights of the contributions of the optical path-length effect and the polarization and scattering of light leaving the films to the lateral response artifact have been estimated to be of the same order of magnitude. Mathematical models of these causes for the parabolic shape of function OD( x ) are given as appendices.